(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: The foot combines mechanical complexities with structural strength to withstand pressure and the metatarsal fat pads play a major role in this. Methods Material: In this study, we determined the metatarsal fat pad thickness of 40 male students that constituted a control group and an age-matched 40 male auto mechanic artisans within Abakaliki metropolis, southeast Nigeria, which served as the quasi-experimental group. Evaluation was made using a brightness mode ultrasound system. Their weights, heights, foot length, foot breadth and mid foot circumference were measured. Results: Results show a significant (P<0.05) difference in the mid-foot circumference and metatarsal fat pad thickness between the control (9.99±0.55cm and 2.04±0.35mm respectively) and artisans (9.58±2.0.59cm and 2.50±2.0.38mm respectively). However, there was no significant (P>0.05) differences in the foot breadth and length between the control (9.86±0.84cm and 26.96±1.03cm) and artisans (10.03±0.54cm and 26.16±1.39cm). Conclusion: These findings indicate that occupation related physical activity that increases plantar pressure can induce an unprecedented thickening of the Metatarsal fat pads thereby reducing elasticity and shock absorbing ability of the fat pads. This could trigger the development of overuse injuries of the foot and plantar foot ulcers. The assessment could also serve as a guidepost in the biomechanical evaluation of the metatarsal fat pad thickness. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.245-250